Ovarian performance of Barbados Blackbelly and Dorper crossbred ewes in the mirror of body conditions - Gyimóthy, Gergely; Harangi, Sándor; Kovács, András (Acta Agraria Debreceniensis, 2010)
The aim of examination was to detect the puberty and to follow the ovarian cycle of Barbados Blackbelly×Dorper ewes in connection with their body conditions and the effects of meteorological parameters. The blood samples had been taken from 17th of November 2008 untill 08th of June 2009 for analyzing the progesteron concentrations, establishing whether they showed perpetual ovarian performance or not. The end of examinationwas timed due to releasing the ram in middle of May 2009.The daily avarage bodyweight-growth is well featured by the bodyweight tendence. The body conditions were evaluated by ultrasound tissue examination. During the full length of the examination the avarage daily temperature, the avarage humidity level and also the number of daily sunlighted hours were served by the Agrometeorological Observatory of the University of Debrecen.The bodyweight tendence and the meteorological parameters were correlated to the breeding season of ewes. In conclusion the bodyweights and their tendences at the young age and the body condition parameters measured at certain anatomical areas can influence the length of the breeding season of the ewes. However the number of daily avarage sunlighted hours, the daily avarage temperature and also the humidity did not effect the cyclic ovarian perfomance of the Barbados Blackbelly×Dorper ewes in Hungary.